High-dose chemotherapy with carmustine, etoposide, cytarabine and melphalan followed by autologous stem cell transplant is an effective treatment for elderly patients with poor-prognosis lymphoma. Issue 8 (3rd August 2015) - Martin, Nicolas; Borchiellini, Delphine; Coso, Diane; Gastaud, Lauris; Boscagli, Annick; Saudes, Laurence; Re, Daniel; Gutnecht, Jean; Garnier, Georges; Petit, Emmanuel; Barriere, Jèrôme; Naman, Hervé; et al.
Abstract : Autologous stem cell transplant (ASCT) after high-dose chemotherapy (HDT) increases overall survival when used in relapsed non-Hodgkin lymphoma (NHL) in patients under 65 years old. Limited experience is available for older patients. We present a retrospective analysis of 73 consecutive patients aged over 65 years treated for aggressive or relapsed lymphoma by HDT with carmustine, etoposide, cytarabine and melphalan (BEAM) at full dosage followed by ASCT. Patient data were obtained from medical charts from two institutions. Median age was 67 years (65–74). Significant comorbidities were present in 24.7% of patients. The median number of days for grade 4 neutropenia was 9 (5–18). The early treatment-related mortality rate (< 100 days) was 2.7%. The estimated 2-year progression-free survival and overall survival rates were 67.2% and 78.5%, respectively. In conclusion, the full-dose HDT-ASCT regimen is feasible, safe and efficient in selected patients over 65 years old.